Serotonin syndrome: a rare undiagnosed cause of hyperpyrexia - Hamdy Ibrahim; Safwat Abdel Maksod; Magdy Khorshed; Hanan Rady; Ahmed Alsisi; Adel Mohamed; Omar Alkassas; Marwa Haron; Suzan Saied (SpringerOpen, 2023)
Abstract Serotonin syndrome (SS) is a rare but potentially life-threatening condition, and it is caused by increasing serotonergic activities. It is an underdiagnosed and under-reported condition. Clinical manifestations can range from mild to moderate to severe symptoms. The intensity of symptoms reflects the degree of serotonin toxicity, and mild serotonin syndrome is easily overlooked by physicians. Severe serotonin toxicity typically occurs to a combination of serotonergic agents. Herein, we describe a case of severe serotonin toxicity in a 38-year-old Egyptian male with a history of generalized anxiety disorder and depression. With increased depressive symptoms, he received 20 mg of fluoxetine daily, and the symptoms developed 1 month after starting fluoxetine, which is the uncommon onset of presentation. The patient was already on tramadol for chronic low backache. The aim is to increase awareness of the syndrome among physicians and neuropsychiatrists.